Dietary magnesium supplementation inhibits abdominal vascular calcification in an experimental animal model of chronic kidney disease. Issue 6 (3rd February 2022) - Leenders, Nicoline H J; Bos, Caro; Hoekstra, Tiny; Schurgers, Leon J; Vervloet, Marc G; Hoenderop, Joost G J
ABSTRACT: Background: Vascular calcification is a key process involved in cardiovascular morbidity and mortality in patients with chronic kidney disease (CKD). Magnesium supplementation may counteract vascular calcification. In this study we aimed to determine whether increased dietary magnesium intake inhibits vascular calcification in CKD in vivo and explore the mechanisms underlying these effects. Methods: Sprague Dawley rats were partially nephrectomized and fed a diet with high phosphate and either high or normal magnesium content for 16 weeks. The primary outcome was the tissue calcium content of the aorta in the high versus normal dietary magnesium group. In addition, we analysed plasma mineral concentrations, aortic vascular calcification identified with von Kossa staining, calcium apposition time and aortic expression of genes related to vascular calcification. Results: The number of animals in the highest tissue calcium content tertile was significantly lower in the abdominal aorta [1 (10%) versus 6 (55%); P  = .03] in the high versus normal dietary magnesium group, but did not differ in the aortic arch and thoracic aorta. Von Kossa staining and calcium apposition time corresponded to these results. The median tissue calcium content was not significantly different between the groups. Serum phosphate concentrations and expression of osteogenic markers in the aorta did not differ between the groups. Conclusions: This study demonstrates that increased dietary magnesium inhibits abdominal vascular calcification in an experimental animal model of CKD in vivo . These are promising results for CKD patients and further study is needed to identify the mechanisms involved and to determine the clinical relevance in patients. Graphical Abstract: